2005
DOI: 10.1063/1.1891346
|View full text |Cite
|
Sign up to set email alerts
|

Versatile force–feedback manipulator for nanotechnology applications

Abstract: A nanoscale manipulation system has been designed and built through the integration of a force–feedback haptic device and a commercial atomic force microscope. The force–feedback interaction provides a very intuitive, efficient and reliable way for quick manipulation of nanoscale objects. Unlike other nanomanipulators, ours allows the user to feel the actual tip–sample interaction during the manipulation process. Various modes of manipulation have been implemented and evaluated. As a proof of concept, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Fortunately, this issue has been resolved in the haptic-STM interface presented below. Finally, Jobin et al 10 successfully demonstrated the operation of an AFM in closed-loop operation controlled with a haptic device in performing manipulation of carbon nanotubes and silica beads.…”
Section: Reviewmentioning
confidence: 97%
“…Fortunately, this issue has been resolved in the haptic-STM interface presented below. Finally, Jobin et al 10 successfully demonstrated the operation of an AFM in closed-loop operation controlled with a haptic device in performing manipulation of carbon nanotubes and silica beads.…”
Section: Reviewmentioning
confidence: 97%
“…However, there are other manipulation techniques which have enabled haptic interface to the user. Marc et al 15 demonstrated sensing AFM cantilever forces and feeding the response to the haptic device enabling user to feel the small forces scaled up. A similar forcefeedback system has been reported in Fok et al 22 It is desirable to the user manipulating micro-objects to perceive the micro/nanohandling forces.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the commercially available products for in vitro fertilization are manufactured by Applied Scientific Instrumentation, 12 Eppendorf, 13 and Harvard Apparatus. 14 Other methods involving atomic force microscope ͑AFM͒ based manipulation systems 15 and microgripper designs 16,3 have utilized force controlled manipulation. The AFM based systems have demonstrated manipulation at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…The haptic technologies have been introduced in nanometer-scale manipulations based on atomic force microscopes (AFMs). By using AFMs coupled with the haptic devices, nanometer scale manipulations have been carried out to investigate structures and detailed properties of nanomaterials such as carbon nanotubes [7][8][9][10][11], fibrin fibers [12,13] and DNA [13,14]. The various haptic feedback techniques using virtual reality have been developed to realize more sophisticate and accurate operation [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%